2022
DOI: 10.3389/fphar.2022.878898
|View full text |Cite
|
Sign up to set email alerts
|

Rhoifolin Alleviates Alcoholic Liver Disease In Vivo and In Vitro via Inhibition of the TLR4/NF-κB Signaling Pathway

Abstract: Background: Alcoholic liver disease (ALD) is a common chronic liver disorder worldwide, which is detrimental to human health. A preliminary study showed that the total flavonoids within Citrus grandis “Tomentosa” exerted a remarkable effect on the treatment of experimental ALD. However, the active substances of Citrus grandis “Tomentosa” were not elucidated. Rhoifolin (ROF) is a flavonoid component present in high levels. Therefore, this research aimed to evaluate the hepatoprotective effects of ROF and its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…54 TLR4 triggers the production of multiple inflammatory factors through activation of the NF-κB pathway, which is closely related to the inflammatory response in alcoholic liver injury. 53,55 Molecular docking experiments revealed that the docking binding energies of HGEPGQQQR, VAPFPEVFGK and HNVADPQR with TLR4 () were −6.5 kcal mol −1 , −6.7 kcal mol −1 , and −5.9 kcal mol −1 , respectively. HGEPGQQQQR forms hydrogen bonds with Glu142, Gln163, Ser140, Asn143, Ala139, Leu117, Thr136, Gln115, and Ile114 residues of TLR4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 TLR4 triggers the production of multiple inflammatory factors through activation of the NF-κB pathway, which is closely related to the inflammatory response in alcoholic liver injury. 53,55 Molecular docking experiments revealed that the docking binding energies of HGEPGQQQR, VAPFPEVFGK and HNVADPQR with TLR4 () were −6.5 kcal mol −1 , −6.7 kcal mol −1 , and −5.9 kcal mol −1 , respectively. HGEPGQQQQR forms hydrogen bonds with Glu142, Gln163, Ser140, Asn143, Ala139, Leu117, Thr136, Gln115, and Ile114 residues of TLR4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…52 CYP2E1 catalyzes the oxidation of ethanol to acetaldehyde, and its metabolites can produce hepatocytotoxicity and increase the risk of developing ALD. 53 Molecular docking revealed that the docking binding energies of HGEPGQQQR, VAPFPEVFGK and HNVADPQR with CYP2E1 (3E6I) were −7.7 kcal mol −1 , −8.2 kcal mol −1 , and −8.2 kcal mol −1 , respectively, suggesting that all three peptides could effectively bind to CYP2E1 and form stable conformations. As can be seen in Fig.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Subsequently, the mRNA expression of inflammatory cytokines, including TNF-α, IL-1β, and IL-6, was notably suppressed in alcohol-treated HepG2 cells and the livers of chronic-binge alcohol-fed mice. Previous studies have suggested that NFκB activation is responsible for regulating the expression of TNF-α, IL-6, and IL-1β in the livers of alcohol-treated mice . Inflammatory stimuli further enhance COX-2 expression, contributing to liver injury.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have suggested that NFκB activation is responsible for regulating the expression of TNF-α, IL-6, and IL-1β in the livers of alcohol-treated mice. 30 Inflammatory stimuli further enhance COX-2 expression, contributing to liver injury. Additionally, multiple studies have demonstrated that exposure to alcohol increases the levels of P-Akt, which plays a crucial role as an upstream activator in the inflammatory response involving NFκB in the liver.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ethanol metabolism generates acetaldehyde, disrupting the equilibrium between the body’s oxidative and peroxide systems, resulting in oxidative stress. This imbalance contributes to increased levels of cytotoxic oxidative product MDA in liver tissues, increased ROS content, compromised antioxidant capacity, reduced free-radical scavenging ability, and lipid peroxidation of liver cell membranes, collectively causing liver cell damage ( Mai et al, 2022 ). In the present study, the EtOH group showed significantly increased ALT and AST levels in HepG2 cells compared to the control group, indicating liver cell damage.…”
Section: Discussionmentioning
confidence: 99%